Effects of Changes in Colored Light on Brain and Calf Muscle Blood Concentration and Oxygenation - J. Weinzirl; M. Wolf; P. Heusser; M. Nelle; U. Wolf (The Scientific World Journal)
Color light therapy is a therapeutic method in complementary medicine. In color therapy, light of two contrasting colors is often applied in a sequential order. The aim of this study was to investigate possible physiological effects, i.e., changes in the blood volume and oxygenation in the brain and calf muscle of healthy subjects who were exposed to red and blue light in sequential order. The hypothesis was that if a subject is first exposed to blue and then red light, the effect of the red light will be enhanced due to the contrastingly different characteristics of the two colors. The same was expected for blue light, if first exposing a subject to red and then to blue light. Twelve healthy volunteers (six male, six female) were measured twice on two different days by near-infrared spectroscopy during exposure to colored light. Two sequences of colored light were applied in a controlled, randomized, crossover design: first blue, then red, and vice versa. For the brain and muscle, the results showed no significant differences in blood volume and oxygenation between the two sequences, and a high interindividual physiological variability. Thus, the hypothesis had to be rejected. Comparing these data to results from a previous study, where subjects were exposed to blue and red light without sequential color changes, shows that the results of the current study appear to be similar to those of red light exposure. This may indicate that the exposure to red light was preponderant and thus effects of blue light were outweighed.